Real-time monitoring of respiratory absorption factors of volatile organic compounds in ambient air by proton transfer reaction time-of-flight mass spectrometry - Huang, Zhonghui; Zhang, Yanli; Yan, Qiong; Zhang, Zhou; Wang, Xinming (Journal of hazardous materials, 2016)
[Display omitted] ⿢Real-time monitoring of VOC respiratory absorption factors (AFs) by PTR-TOF-MS.⿢A homemade breath sampling device with a buffer tube to optimize signal peaks.⿢Isoprene in breath air was an excellent breath phase tracer.⿢BTEX respiratory AFs less than 100% or 90% assumed previously for risk assessment.⿢Female subjects showed significantly higher respiratory AFs of BETX than male ones. Respiratory absorption factors (AFs) are essential parameters in the evaluation of human health risks from toxic volatile organic compounds (VOCs) in ambient air. A method for the real time monitoring of VOCs in inhaled and exhaled air by proton transfer reaction time-of-flight mass spectrometry (PTR-TOF-MS) has been developed to permit the calculation of respiratory AFs of VOCs. Isoprene was found to be a better breath tracer than O2, CO2, humidity, or acetone for distinguishing between the expiratory and inspiratory phases, and a homemade online breath sampling device with a buffer tube was used to optimize signal peak shapes. Preliminary tests with seven subjects exposed to aromatic hydrocarbons in an indoor environment revealed mean respiratory AFs of 55.0%, 55.9%, and 66.9% for benzene, toluene, and C8-aromatics (ethylbenzene and xylenes), respectively. These AFs were lower than the values of 90% or 100% used in previous studies when assessing the health risks of inhalation exposure to hazardous VOCs. The mean respiratory AFs of benzene, toluene and C8-aromatics were 66.5%, 70.2% and 82.3% for the three female subjects; they were noticeably much higher than that of 46.4%, 45.2% and 55.3%, respectively, for the four male subjects.